Modeling the Potential for Thermal Concentrating Solar Power Technologies - Zhang, Y. B.; Smith, S. J.; Kyle, G. P.; Stackhouse, P. W. (2012)
In this paper we explore the tradeoffs between thermal storage capacity, cost, and other system parameters in order to examine possible evolutionary pathways for thermal concentrating solar power (CSP) technologies A representation of CSP performance that is suitable for incorporation into economic modeling tools is developed We also combined existing data in order to estimate the global solar resource characteristics needed for analysis of CSP technologies We find that, as the fraction of electricity supplied by CSP technologies grows, the application of thermal CSP technologies might progress from current hybrid plants, to plants with a modest amount of thermal storage, and potentially even to plants with sufficient thermal storage to provide base load generation capacity. The regional and global potential of thermal CSP technologies was then examined using the GCAM long-term integrated assessment model. (C) 2010 Elsevier Ltd All rights reserved